Protective effects of 17 beta-estradiol on endothelial function injured by oxidized low-density lipoproteins - Peng Chang-Fu; Li Yuan-Jian; Deng Han-Wu; Xiong Xiao-Ming (Acta Pharmacologica Sinica, 2016)
AIM: To test the protective effects of 17 beta-estradiol against endothelial cell damages due to oxidized low-density lipoproteins (LDL) and lysophosphatidylcholine (LPC), a principal component of oxidized LDL. METHODS: After the tension was increased by phenylephrine, the effects of oxidized LDL or LPC on the vasorelaxation responses to acetylcholine (ACh) were investigated in the isolated rabbit thoracic aortas. RESULTS: 17 beta-Estradiol attenuated the inhibition of vasorelaxation responses to ACh by oxidized LDL or LPC in a concentration-dependent manner. However, the protective effect of 17 beta-estradiol was partially attenuated by indometacin (10 mumol.L-1), a cyclooxygenase inhibitor. CONCLUSION: 17 beta-Estradiol possesses protective effects on the endothelium against injury elicited by oxidized LDL or LPC, which may be related to its stimulation of epoprostenol production.